1997
DOI: 10.1902/jop.1997.68.2.145
|View full text |Cite
|
Sign up to set email alerts
|

The Thickness of Masticatory Mucosa in the Human Hard Palate and Tuberosity as Potential Donor Sites for Ridge Augmentation Procedures

Abstract: The aim of the present investigation was to clinically determine the thickness of masticatory mucosa in the hard palate and tuberosity as potential donor sites for ridge augmentation procedures. In 31 periodontally healthy, fully dentate subjects the masticatory mucosa thickness was assessed by bone sounding with a periodontal probe. Eighteen standard measurement points were defined in the hard palate, located on 3 lines which ran at different distances parallel to the gingival margin. Six positions were desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
153
9
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(198 citation statements)
references
References 19 publications
23
153
9
13
Order By: Relevance
“…This was in accord with the results of a former study. 25 The PMM thickness between 4 mm and 8 mm below the gingival crest, the areas between the anterior teeth at the level of 4 mm below the gingival crest, and the areas between the posterior teeth at the level of 8 mm below the gingival crest had significantly thicker soft tissue than did the corresponding areas (Table 2). Wara-aswapati et al 19 reported results similar to those of this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was in accord with the results of a former study. 25 The PMM thickness between 4 mm and 8 mm below the gingival crest, the areas between the anterior teeth at the level of 4 mm below the gingival crest, and the areas between the posterior teeth at the level of 8 mm below the gingival crest had significantly thicker soft tissue than did the corresponding areas (Table 2). Wara-aswapati et al 19 reported results similar to those of this study.…”
Section: Discussionmentioning
confidence: 94%
“…20,21 Finally, there is direct measurement using an ultrasonic device such as an ultrasonic gingival-thickness meter (SDM, KRUPP Corporation, Essen, Germany; Figure 1), which has excellent convenience, repeatability, reliability, and accuracy. [22][23][24][25][26][27][28][29] The SDM ultrasonic gingival-thickness meter works by measuring the time between when an ultrasonic wave is emitted and when it has passed through the oral mucosa and is reflected back from the bone surface. The meter's monitor displays the soft-tissue thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Knobloch ve ark. 19 kırılmaya karşı dayanıklılığı tespit etmenin materyalin klinik performansını tahmin etmeye yardımcı olacağını söylemek-tedir. O nedenle çiğneme kuvvetlerinin baskısı altında hangi materyalin daha çok direnç göstereceğine ışık tutacağı düşünülen basma dayanıklılığı testlerinde farklı doldurucu boyutları ve morfolojilerindeki materyaller incelenmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…In the literature, the thickness of a masticatory mucosa is evaluated by both invasive and non-invasive methods. The invasive method of assessing masticatory mucosa includes conventional histology on cadaver jaws, while a few others used injection needle or probe, histologic sections or cephalometric radiographs (Studer et al 1997). Although the thickness was assessed by the bone sounding technique or the transgingival probing method in dentate subjects, only the palatal masticatory mucosa was evaluated (Muller et al 2000).…”
Section: Introductionmentioning
confidence: 99%